The Influence of Financial Literacy, Income, and Lifestyle on Personal Financial Management with Self Control as a Moderating Variable - Hari Wahyuni (University of Merdeka Malang, 2024)
This research aims to examine the influence of financial literacy, income, and lifestyle on personal financial management, with self-control as a moderating variable. To test hypotheses and explain correlations between variables, explanatory research methods are employed. 125 Merdeka University Pasuruan Faculty of Economics students from semesters five and seven who had taken financial planning courses made up the study's population. Purposive sampling, which uses students who have studied financial planning and are currently employed, is the sampling strategy used. The quota sampling approach was used to pick a sample of sixty-six pupils. The study's findings show that lifestyle, income, and financial literacy all positively impact an individual's ability to manage their finances, with self-control remaining unable to mitigate the effects on students' personal financial management. Low-income levels and a straightforward lifestyle that promotes personal money management are to blame for this. Therefore, more studies must be done on other factors that can moderate the success of student financial management.